Multiple Variations of Branches of Abdominal Aorta - Salve, V M; Ratanprabha, C (Kathmandu University Medical Journal, 2012)
The Abdominal aorta and its major branches supply oxygenated blood to nearly all the organs in the abdominal cavity. During routine dissection (January 2009) of a middle aged male cadaver at Dr. PSIMS, Gannavaram, Krishna Dist. (INDIA), the following variations of branches of abdominal aorta were found. The coeliac trunk gave off three branches. The first branch was left inferior phrenic artery which arose directly from coeliac trunk. The second branch bifurcates into left gastric artery and accessory hepatic artery for left lobe of liver. The second branch gave off splenic artery and common hepatic artery. The right testicular artery took its origin from right aberrant renal artery. This variation was associated with the presence of bilateral aberrant renal arteries for lower poles of both kidneys arising from abdominal aorta and aberrant renal arteries bilateral for upper poles originating from the renal arteries. Anatomical variation of testicular arteries is reported to be 4.7 %. Apart from creating hazards during abdominal surgery, vascular variation can also become a technical problem for infusion therapy and chemoembolisation of neoplasm in the liver.http://dx.doi.org/10.3126/kumj.v9i1.6268 Kathmandu Univ Med J 2011;9(1):72-6